2013
DOI: 10.1038/ng.2570
|View full text |Cite
|
Sign up to set email alerts
|

A detrimental mitochondrial-nuclear interaction causes cytoplasmic male sterility in rice

Abstract: Plant cytoplasmic male sterility (CMS) results from incompatibilities between the organellar and nuclear genomes and prevents self pollination, enabling hybrid crop breeding to increase yields. The Wild Abortive CMS (CMS-WA) has been exploited in the majority of 'three-line' hybrid rice production since the 1970s, but the molecular basis of this trait remains unknown. Here we report that a new mitochondrial gene, WA352, which originated recently in wild rice, confers CMS-WA because the protein it encodes inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
453
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 451 publications
(466 citation statements)
references
References 38 publications
8
453
2
3
Order By: Relevance
“…indica) CMS-WA line Zhenshan 97A (ZS97A) ( Figure 1A and 1B). The WA352c ORF is located downstream of rpl5, and consists of four segments: 284s, cs3 (previously defined as unknown origin and orf224-homologous sequence [10]), cs2 and cs1 (previously defined as an orf288-homologous sequence [10]). The 284s segment is identical to the promoter/5′-ORF of a putative mitochondrial ORF orf284, and cs1-cs3 and the downstream sequences cs4-cs6 are conserved in the mitochondrial genomes of the Oryza species and other plants (such as maize, sorghum, wheat, and soybean) (see below).…”
Section: Identification Of Cms-related Recombinant Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…indica) CMS-WA line Zhenshan 97A (ZS97A) ( Figure 1A and 1B). The WA352c ORF is located downstream of rpl5, and consists of four segments: 284s, cs3 (previously defined as unknown origin and orf224-homologous sequence [10]), cs2 and cs1 (previously defined as an orf288-homologous sequence [10]). The 284s segment is identical to the promoter/5′-ORF of a putative mitochondrial ORF orf284, and cs1-cs3 and the downstream sequences cs4-cs6 are conserved in the mitochondrial genomes of the Oryza species and other plants (such as maize, sorghum, wheat, and soybean) (see below).…”
Section: Identification Of Cms-related Recombinant Structuresmentioning
confidence: 99%
“…We previously identified the CMS-WA gene WA352 (here renamed WA352c, see below) and revealed that WA352c causes CMS by interaction with the nucleus-encoded, highly conserved mitochondrial protein COX11, leading to premature programmed cell death in the anther tapetum and defective pollen development. Male fertility of WA352c-carrying hybrids can be restored by the dominant restorer genes Rf4 and Rf3, which suppress WA352c function at the mRNA and protein levels, respectively, in diploid anther-wall cells of the hybrids (i.e., in a sporophytic manner) [10,11]. We noted that the WA352c-containing structure in the mitochondrial genome (including the upstream and downstream flanking regions) consists of multiple segments that are homologous to different sequences of the mitochondrial genomes in wild rice species, suggesting a complicated origin through DNA recombination and rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…CMS-WA has the CMS cytoplasm of a male sterile O. rufipogon plant, and the sterility gene responsible had previously been identified [7]. The new paper calls it WA352c, as it encodes 352 amino acids; the protein product was shown to accumulate specifically in tapetal cells, where it interacts with the highly conserved mitochondrial protein COX11 (encoded by a nuclear gene), impairing COX11's function, leading to pollen abortion.…”
mentioning
confidence: 99%
“…Figure 4 in the paper, omitting amino acid substitutions, to show just two of the inferred major rearrangements that can generate the many variants found in O. rufipogon; their frequencies in the sample of 200 plants studied from this species are also indicated (they sum to < 100% as a few structures rarely found in O. rufipogon are omitted). Different mitochondrial genome regions are indicated by horizontal lines in different colors, and thin black lines indicate other parts of the genome, with symbols to indicate gaps where the largescale organization is not known (the orders of the regions separated by gaps are unknown; for instance, except for the structure at the top, the cox1 gene was transferred to another location in the genome [7,12]). The top part of the diagram shows the probable ancestral mitochondrial genome structure (now rare in O. rufipogon); the region that carried the cs1 sequence is also seen in other Oryza species and other grasses, but cs1 is physically separated from the ORF that is involved in the hypothesized rearrangements that yielded a new, chimeric ORF.…”
mentioning
confidence: 99%
“…The mechanism underlying CMS had remained unclear for many years. Recently, however, a breakthrough was made in rice [17,18]. Members of the Cruciferae show considerable heterosis, so male-sterile lines are very useful for producing F1 hybrid cruciferae crops.…”
mentioning
confidence: 99%